Fall from grace: the reception of Guido Reni in Britain from the seventeenth to the nineteenth century - Parrish, Amy (2020)
This thesis concerns an extreme revolution in taste in European art: the transformation of British attitudes towards the seventeenth-century Bolognese artist Guido Reni (1575–1642). Reni was one of the most collectable and revered artists in seventeenth- and eighteenth-century Britain. However, his reputation suffered a dramatic decline and in the nineteenth century he became deeply suspect in the British popular imagination. His works were subject to critical reassessment and he was judged by a new standard of taste. This thesis sets out to understand this rise and fall in Reni’s reputation. It explores how Reni’s reputation was first established in Britain in the seventeenth century. Various aspects of his high status in the eighteenth century are considered, including the collecting of his works by prominent aristocrats and the attraction of copies after his paintings for a wide variety of his individuals. It is argued that the decline in Reni’s reputation occurred much earlier than previously acknowledged and can first be observed in the eighteenth century. It is particularly associated with a series of observations made by various members of the Royal Academy at the turn of the nineteenth century. The continuing deterioration in Reni’s reputation in the nineteenth century is considered and shown to be less clear-cut than is usually assumed. Responses to Reni are shown to reflect wider historical changes in Britain and transformations in the nature of artistic discourse.